2014
DOI: 10.3732/ajb.1300388
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of the endemic and endangered Vriesea minarum (Bromeliaceae) in the Iron Quadrangle, Espinhaço Range, Brazil

Abstract: • Premise of the study: Knowledge about genetic variability in plant populations is one of the main branches of conservation genetics, linking genetic data to conservation strategies. Vriesea minarum is a bromeliad endemic to the Iron Quadrangle region (southeastern Brazil), occurring on mountaintop rock outcrops. It is listed as endangered due to habitat loss, particularly from iron ore mining. Thus, determining the structure and genetic diversity of V. minarum populations could help develop strategies to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 57 publications
(60 reference statements)
3
25
1
Order By: Relevance
“…Unlike the pattern found for Alcantarea imperialis (Carrière) JR Grant and Aechmea geniculata (Wawra) JR Grant (Barbará et al, 2007), in Vriesea gigantea , and also Vriesea minarum (Lavor et al, 2014), the observed heterozygosity was lower than expected because of a deficit of heterozygotes. These data further suggest that an excess of homozygotes could be due to selfing or biparental inbreeding, since V. minarum exhibits a mixed reproductive strategy (outcrossing + self-compatibility), or due to a feature of the subfamily Tillandsioideae.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…Unlike the pattern found for Alcantarea imperialis (Carrière) JR Grant and Aechmea geniculata (Wawra) JR Grant (Barbará et al, 2007), in Vriesea gigantea , and also Vriesea minarum (Lavor et al, 2014), the observed heterozygosity was lower than expected because of a deficit of heterozygotes. These data further suggest that an excess of homozygotes could be due to selfing or biparental inbreeding, since V. minarum exhibits a mixed reproductive strategy (outcrossing + self-compatibility), or due to a feature of the subfamily Tillandsioideae.…”
Section: Discussioncontrasting
confidence: 85%
“…Plants in the Bromeliaceae family provide excellent models for the study of genetic diversity (Zanella et al, 2012;Hmeljevski et al, 2013), population genetics (Lavor et al, 2014), as well as the divergence between populations and species (Sarthou et al, 2001;Barbará et al, 2007;Palma-Silva et al, 2009). Bromeliads are an important and characteristic element of Neotropical forests, especially in the Brazilian Atlantic Forest (BAF), where they are among those families with the greatest richness and diversity (Martinelli et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These markers have proved a useful tool for determining the genetic structure in many plant species (Mattioni et al 2013, Lavor et al 2014, Noormohammadi et al 2014, Shivaprakash et al 2014. In wild Phaseolus lunatus, SSRs have been used to determine the genetic structure in populations of Costa Rica and Mexico, showing high genetic differentiation between wild populations of P. lunatus and clustering patterns based on geographical isolation and low levels of gene flow (Ouédraogo et al 2005, Martínez-Castillo et al 2006.…”
Section: K Pedro Jesús Ruiz-gil Et Almentioning
confidence: 99%